Literasi Digital sebagai Upaya Membangun Karakter Masyarakat Digital - Isabella, Isabella; Iriyani, Atrika; Puji Lestari, Delfiazi (Universitas Indo Global Mandiri, 2023)
In an effort to shape the culture of a digital society in Palembang, this study examines digital literacy. The purpose of this study is: Analyze the supporting and impeding factors for this program. Identify the implementation of digital literacy programs as an endeavor to develop the character of the digital society in the city of Palembang. In this study, a qualitative descriptive methodology was utilized to describe and assess how the Digital Literacy program was implemented in an effort to shape the characteristics of a digital society in Palembang. The analytical methods employed involve qualitative data analysis methods using FGD, interviews, and documentation. Additionally, the NVivo 12 Plus and SmartPLS analysis complement this research data. The theory applied is Merilee S. Grindle's theory of policy implementation. Digital Skills, Digital Culture, Digital Ethics, and Digital Safety are some of the supporting indicators in the Kominfo RI framework for digital literacy. The study's findings show that promoting digital literacy is a movement that cannot be carried out by one institution alone; instead, the government, society, and stakeholders all need to get involved if we want to avoid falling behind. People who are learning to use digital operating systems in daily life are concerned with developing their digital skills. The government is known to be interested in creating news in the media or online, therefore it requires journalists who are impartial and can speak the truth without instilling fear. Still other discoveries.